Expression of indoleamine 2, 3-dioxygenase in leukemic cells indicates an unfavorable prognosis in acute myeloid leukemia patients with intermediate-risk cytogenetics. Issue 5 (May 2015) - Fukuno, Kenji; Hara, Takeshi; Tsurumi, Hisashi; Shibata, Yuhei; Mabuchi, Ryoko; Nakamura, Nobuhiko; Kitagawa, Junichi; Shimizu, Masahito; Ito, Hiroyasu; Saito, Kuniaki; Moriwaki, Hisataka
Abstract The immunomodulatory effects of indoleamine 2, 3-dioxygenase (IDO) are ascribed to its ability to catalyze breakdown of the essential amino acid l-tryptophan. We applied reverse transcription-polymerase chain reaction (RT-PCR) to examine IDO mRNA expression in acute myeloid leukemia (AML) blasts, and investigated its clinical significance. We enrolled 62 patients with AML between April 2005 and March 2013. Bone marrow-derived mononuclear fractions were separated and extracted mRNA was amplified by PCR. RT-PCR showed that the bone marrow of 23 patients expressed IDO mRNA but not in 39. IDO mRNA expression did not significantly differ among cytogenetic risk profiles. The 3-year overall survival rates for patients with and without IDO mRNA expression were 39% and 74%, respectively (p < 0.005). The rates for patients with intermediate-risk cytogenetics with and without IDO mRNA expression were 16% and 70%, respectively (p < 0.005). The expression of IDO mRNA was associated with a poor prognosis of AML.